Oxy-imino saccharidic derivatives as a new structural class of aldose reductase inhibitors endowed with anti-oxidant activity. (1st January 2020) - D'Andrea, Felicia; Sartini, Stefania; Piano, Ilaria; Franceschi, Matteo; Quattrini, Luca; Guazzelli, Lorenzo; Ciccone, Lidia; Orlandini, Elisabetta; Gargini, Claudia; La Motta, Concettina; Nencetti, Susanna
Abstract: Aldose reductase is a key enzyme in the development of long term diabetic complications and its inhibition represents a viable therapeutic solution for people affected by these pathologies. Therefore, the search for effective aldose reductase inhibitors is a timely and pressing challenge. Herein we describe the access to a novel class of oxyimino derivatives, obtained by reaction of a 1, 5-dicarbonyl substrate with O -(arylmethyl)hydroxylamines. The synthesised compounds proved to be active against the target enzyme. The best performing inhibitor, compound ( Z )-8, proved also to reduce both cell death and the apoptotic process when tested in an in vitro model of diabetic retinopathy made of photoreceptor-like 661w cell line exposed to high-glucose medium, counteracting oxidative stress triggered by hyperglycaemic conditions.